Democracy and the Media The Year in C-SPAN Archives Research, Volume 7 - Browning, Robert K. (Purdue University Press, 2021)
Volume 7 of The Year in C-SPAN Archives Research series focuses on the relationship between democracy and the media. Using the extensive collection of the C-SPAN Video Library, chapters cover Trump political rallies, congressional references of late-night comedy, responses of African American congresswomen to COVID-19 bills, and congressional attacks on the media through floor speeches in the House of Representatives and Senate. The C-SPAN Video Library is unique because there is no other research collection that is based on video research of contemporary politics. Methodologically distinctive, much of the research uses new techniques to analyze video, text, and spoken words of political leaders. No other book examines such a wide range of topics-from immigration to climate change to race relations-using video as the basis for research.